Sao Tome and Principe : Background Papers and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 1995)
This paper describes economic and financial developments in Sao Tome and Principe during the 1990s. The economic and financial performance deteriorated sharply during 1994, owing to excessively expansionary fiscal and monetary policies. Although real GDP grew virtually at the same rate as in 1993, inflation almost doubled. The fiscal deficit increased markedly compared with 1993, and was financed to a much greater extent than in the past by net credit from the banking system. Nonetheless, the balance of payments improved, primarily owing to higher inflows of private and official unrequited transfers.